Poly(curcumin β-amino ester)-Based Tablet Formulation for a Sustained Release of Curcumin - Vinod S. Patil; Benjamin C. Burdette; J. Zach Hilt; Douglass S. Kalika; Thomas D. Dziubla (Gels, 2022)
Oral drug delivery remains the most common and well tolerated method for drug administration. However, its applicability is often limited due to low drug solubility and stability. One approach to overcome the solubility and stability limitations is the use of amorphous polymeric prodrug formulations, such as poly(β-amino ester) (PBAE). PBAE hydrogels, which are biodegradable and pH responsive, have shown promising results for the controlled release of drugs by improving the stability and increasing the solubility of these drugs. In this work, we have evaluated the potential use of PBAE prodrugs in an oral tablet formulation, studying their sustained drug release potential and storage stability. Curcumin, a low solubility, low stability antioxidant drug was used as a model compound. Poly(curcumin β-amino ester) (PCBAE), a crosslinked amorphous network, was synthesized by a previously published method using a commercial diacrylate and a primary diamine, in combination with acrylate-functionalized curcumin. PCBAE-based tablets were made and exhibited a sustained release for 16 h, following the hydrolytic degradation of PCBAE particles into native curcumin. In addition to the release studies, preliminary storage stability was assessed using standard and accelerated stability conditions. As PCBAE degradation is hydrolysis driven, tablet stability was found to be sensitive to moisture.